Analysis of The Use of Learning Facilities to Improve Science Learning Achievement In MTs AL Jihad Kerasaan of Simalungun Regency South Sumatra - Huda, Muhammad Komarul (CV. Inara, 2022)
School is an educational institution in charge of meeting the educational goals that have been entrusted through law. Therefore, efforts are needed to improve the educational quality based on students' achievement, which can be carried out through various ways by the stakeholders in the educational institution. The current research was conducted to identify the relationship between the use of learning facilities and science learning achievement. The method applied is descriptive quantitative using questionnaire data and deep interviews. The total population involved is 407 students, of which 186 of them were selected as the research samples using Proportional Stratified Random Sampling technique. Based on the research, it was revealed that there was a positive relationship between the use of learning facilities and science learning achievement, which is indicated by the correlation test of rxy (0.180) > rtab (0.143). Furthermore, the deep interviews showed that students had difficulty in learning science because there were no laboratory facilities for the practicum as well as the limited infocus tools of only two units of audio-visual media. However, the teacher's improvisation in performing the practicum was categorized as quite good. Eventually, it can be summed up that learning facilities are one of the determining factors in improving student achievement. In this case, it is suggested for further research to add other variables to support the improvement of student achievement.